Hubungan Resiliensi Keluarga Berfokus Pada Sistem Kepercayaan dan Pola Komunikasi dengan Kesejahteraan Fisiologis Pada Pasien dengan Penyakit Kronis - Nor Alifah Ramadhia, Gita; Milasari, Milasari; Afni Oktavia, Nor (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2025)
Chronic diseases require continuous management and often impact patients’ physiological well-being. Family resilience, especially in belief systems and communication patterns, has an important role in supporting adaptation and recovery. This study aimed to examine the relationship between family resilience and physiological well-being in patients with chronic diseases. A quantitative study with a cross-sectional design was conducted on 86 patients at Dr. H. Moch Ansari Saleh General Hospital, Banjarmasin, selected through purposive sampling. Data were collected using the Family Resilience Questionnaire focusing on belief systems and communication patterns, and a physiological well-being instrument. Data analysis was performed using Spearman’s Rho correlation. The findings showed that most respondents had moderate levels of family resilience and physiological well-being. The statistical test results revealed a significant positive correlation between family resilience and physiological well-being (p = 0.000; r = 0.701). These results indicate that the stronger the family’s belief system and communication patterns, the better the physiological health outcomes experienced by patients with chronic diseases. This study highlights the importance of involving families in patient care, especially through interventions that strengthen resilience and communication, to improve treatment adherence and overall health outcomes. Healthcare providers are encouraged to adopt family-centered strategies in chronic disease management